1983
DOI: 10.1113/jphysiol.1983.sp014800
|View full text |Cite
|
Sign up to set email alerts
|

beta‐Adrenoceptor alterations coupled with secretory response in rat parotid tissue.

Abstract: SUMMARY1. Simultaneous studies on the secretary response of amylase and the neurotransmitter receptors ofrat parotid gland, after brieftreatment with agonists, showed selective alteration in /1-adrenoceptors with specific change in amylase secretion, suggesting a regulatory role of the receptors in the secretary response.2. The fl-adrenergic agonist (± )-isoprenaline (IPR) stimulated amylase secretion from rat parotid tissues much more than did the same concentration ofan a-adrenergic or cholinergic agonist.3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
1

Year Published

1985
1985
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 31 publications
1
14
1
Order By: Relevance
“…In rat parotid acinar cells (Fig. 2B), the labeling was especially associated with the apical microvilli, including those situated in the intercellular secretory canaliculi, consistent with previous observations (9). Immunoelectron microscopy also demonstrated that the punctate appearance of the AQP-5 distribution in both glands was due to the clustering of labeling around the microvilli separated by relatively unlabeled nonmicrovillous plasma membrane domains.…”
Section: Subcellular Localization Of Aqp-5 In Salivary Glands By Lighsupporting
confidence: 72%
“…In rat parotid acinar cells (Fig. 2B), the labeling was especially associated with the apical microvilli, including those situated in the intercellular secretory canaliculi, consistent with previous observations (9). Immunoelectron microscopy also demonstrated that the punctate appearance of the AQP-5 distribution in both glands was due to the clustering of labeling around the microvilli separated by relatively unlabeled nonmicrovillous plasma membrane domains.…”
Section: Subcellular Localization Of Aqp-5 In Salivary Glands By Lighsupporting
confidence: 72%
“…Preparation of rat parotid tissue Parotid glands were obtained from male Wistar rats (200-350 g) and small pieces of the tissue were prepared as described previously (Hata et al, 1983). Before experiments, Krebs-Ringer Tris (KRT) solution, consisting of (mM) NaCl 120, KCI 4.8, KH2PO4 1.2, MgSO4 1.2, CaCI2 3.0, Tris HC1 buffer (pH 7.4) 16 and glucose 5, was aerated with 02 and the pieces of parotid tissues were equilibrated with the solution for 20 min at 37°C with shaking.…”
Section: Methodsmentioning
confidence: 99%
“…Other methods and procedures were as described previously (1 ). Procaterol hydrochloride was a gift from Otsuka Pharmaceutical Co. (Tokushima, Japan), terbutaline sulfate was from Fujisawa Pharmaceutical Co. (Osaka, Japan), and prenalterol hydrochloride was from Hassle AB (Molndal, Sweden).…”
mentioning
confidence: 99%
“…The tissue was then washed well with KRT solution, transferred to fresh KRT solution for 10 min at 37'C (resting period), and then challenged by re incubation with the same agonist for 10 min (second incubation). (1). Cyclic AMP in tissues was measured by radioimmunoassay (2) with a Yamasa cyclic AMP assay kit (Yamasa Shoyu, Co., Chiba, Japan).…”
mentioning
confidence: 99%
See 1 more Smart Citation